2008
DOI: 10.1260/135101008785082524
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Resonant and Non-Resonant Components—Part II: Surface Velocity

Abstract: In this second paper, the separation of the resonant and non-resonant components of the mean square velocity of lightweight building elements is investigated for use with EN12354. Two methods for separating the components are presented. The first involves measuring the mean square velocity of a series of panels, each with a different amount of damping. A modified least squares approach is then used. The second method uses the velocity level difference between building elements measured according to EN10848 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…additional uncertainty to the calculations. Two methods of separating the components of the mean square velocity are examined in a companion paper [10]. The correction factors that depend on the mean square velocity of the element include: Nightingale [5]: (9) where η tot is the total loss factor of the element, f c is the critical frequency and and are the resonant and non-resonant components of the mean square velocity of the element, respectively.…”
Section: Correction Factors Based On the Mean Square Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…additional uncertainty to the calculations. Two methods of separating the components of the mean square velocity are examined in a companion paper [10]. The correction factors that depend on the mean square velocity of the element include: Nightingale [5]: (9) where η tot is the total loss factor of the element, f c is the critical frequency and and are the resonant and non-resonant components of the mean square velocity of the element, respectively.…”
Section: Correction Factors Based On the Mean Square Velocitymentioning
confidence: 99%
“…The correction factors that depend on the mean square velocity of the panel were calculated for the steel panel using a modified least square method and data from a series of damped, steel panels as described in a companion paper [10]. The components of the mean square velocity of the MDF panels were not evaluated.…”
Section: Prediction Of the Resonant Component By Correction Factorsmentioning
confidence: 99%
“…Nevertheless, it is known [16,17] that also in the case of homogeneous single panels it is difficult to accurately estimate the radiation efficiency and to calculate the Sound Reduction Index, due to the complexity of the separation of the resonant and non-resonant components. It is well known that the method described in the EN 12354-1 is not suitable for multilayer lightweight structures [18,19], with relatively small dimensions and various edge conditions: only approximate results are given with this method.…”
Section: Estimation Of Different Transmission Pathsmentioning
confidence: 99%
“…The methods which have been proposed in the literature for the calculation of the resonant sound reduction index of lightweight elements will only work with single leaf, homogeneous, isotropic elements with the exception of the correction factor proposed by the Centre Scientifique et Technique du Bâtiment (CSTB). Mahn and Pearse (2008b) and Mahn and Stevenson (2008) tried a number of different methods of determining the resonant sound transmission factors of lightweight elements and found that the different methods resulted in a wide range of values, some of which were invalid.…”
Section: Introductionmentioning
confidence: 99%